High-elasticity modified nylon spandex as well as preparation method and application thereof

By blending modified nylon fiber and spandex fiber and adding modified cellulose and other materials, the existing nylon fabrics have been solved, and fabrics with high elasticity, anti-static and hygroscopic properties have been achieved.

CN119913649AInactive Publication Date: 2025-05-02GUANGDONG JIANDA POLY FIBER TECH IND CO LTD

Patent Information

Application Number
CN202510417406.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing bronchial fabrics are prone to static electricity during friction and have low affinity for water, resulting in poor hygroscopicity.

Method used

By blending the modified nylon fiber and spandex fiber into a yarn at a mass ratio of 3-6:4-7, and adding thermoplastic polyamide elastomer, modified cellulose and polyvinylpyrrolidone to the fibers, the elasticity, hygroscopicity and antistatic properties of the fabric are improved.

Benefits of technology

It has achieved high elasticity, antistatic and hygroscopic fabrics, and is suitable for sportswear, yoga clothing and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of textiles, and discloses high-elasticity modified nylon spandex as well as a preparation method and application thereof. The modified polyamide / spandex prepared by the invention is prepared by blending modified polyamide fibers and spandex fibers into yarns and then spinning the yarns; the modified chinlon / spandex not only has excellent wear resistance of chinlon, but also has excellent elastic property of spandex. The modified polyamide fiber is prepared from the following raw materials in parts by weight: 80 to 120 parts of polyamide chips, 5 to 9 parts of thermoplastic polyamide elastomer, 8 to 12 parts of modified cellulose and 18 to 25 parts of polyvinylpyrrolidone, the added modified cellulose and polyvinylpyrrolidone have a synergistic effect, so that the hygroscopicity, the air permeability and the antistatic property of the modified nylon / spandex are improved. Therefore, the modified brocade / spandex fabric disclosed by the invention has a good application prospect in sportswear.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textiles, and in particular to a high-elastic modified nylon-spandex and a preparation method and application thereof. Background Art

[0002] As a new type of fabric, nylon-spandex is a blend of nylon fiber and spandex fiber. This fabric not only has the advantages of high strength, wear resistance, chemical corrosion resistance and good elasticity of nylon, but also has the high elasticity and recovery of spandex. This fabric is widely used in sportswear, yoga wear, swimwear, underwear and other close-fitting clothing. It is deeply loved by consumers for its softness, comfort, good elasticity and non-deformation characteristics.

[0003] However, this type of fabric still has certain disadvantages, such as: (1) Nylon and spandex are both synthetic fibers, which are prone to generate static electricity during friction, affecting the comfort and safety of wearing. Static electricity accumulation may cause clothing to absorb dust, produce electric shock, and even cause fire hazards under certain circumstances; (2) Nylon and spandex have low affinity for water and are difficult to absorb and retain moisture, which leads to poor hygroscopicity. Therefore, it is necessary to develop a fabric with good hygroscopicity, antistatic and high elasticity to meet people's requirements for clothing fabrics. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a highly elastic modified nylon-ammonia and a preparation method and application thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions: A highly elastic modified nylon-spandex, wherein the modified nylon-spandex is woven from modified nylon-spandex yarn, wherein the modified nylon-spandex yarn is blended with modified nylon fiber and spandex fiber in a mass ratio of 3-6:4-7; The modified nylon fiber comprises the following raw materials in parts by weight: 80-120 parts of nylon chips, 5-9 parts of thermoplastic polyamide elastomer, 8-12 parts of modified cellulose, and 18-25 parts of polyvinyl pyrrolidone; The modified cellulose is prepared by the following steps: Step A1, dispersing cellulose powder in 15wt% sodium hydroxide solution, stirring at 50°C for 5-7h, settling, filtering, washing to neutrality, and drying to obtain alkalized cellulose; Further, in step A1, the mass ratio of cellulose powder to sodium hydroxide solution is 1:20; Step A2, mixing p-toluenesulfonyl chloride in acetonitrile, recorded as solution 1; mixing alkalized cellulose, sodium hydroxide and water, stirring evenly, slowly adding solution 1, reacting in an ice-water bath for 4-6 hours, adding dichloromethane and stirring for 30 minutes, washing, rotary evaporation, and drying to obtain sulfonated cellulose; Further, in step A2, the amount ratio of alkalized cellulose, sodium hydroxide, water, solution 1 and dichloromethane is 5-10 g:1.5-3 g:30 mL:20 mL:50 mL, and the amount ratio of p-toluenesulfonyl chloride and acetonitrile in solution 1 is 0.05-0.15 mol:20 mL; Step A3, adding sodium hydroxide and dimethyl sulfoxide to the sulfonylated cellulose obtained in step A2, mixing and stirring evenly, then adding 1-vinylimidazole, heating to 75-85° C. and reacting for 24-36 hours, distilling under reduced pressure and drying to obtain quaternary ammonium cellulose; Further, in step A3, the molar ratio of 1-vinylimidazole to p-toluenesulfonyl chloride in step A2 is 1:1, and the amount of sodium hydroxide is 0.5-1.5 g; Step A4, under nitrogen conditions, quaternized cellulose, methacryloyloxyethyl trimethyl ammonium chloride and isopropanol were mixed, and stirred at 70° C. for 1 h, azobisisobutyronitrile was added, stirred and reacted for 24 h, and rotary evaporated, filtered and dried to obtain modified cellulose; Furthermore, in step A4, the usage ratio of quaternized cellulose, methacryloyloxyethyltrimethylammonium chloride, isopropyl alcohol and azobisisobutyronitrile is 8-12 g:1-3 g:100 mL:0.2-0.3 g.

[0006] A method for preparing highly elastic modified nylon-ammonia comprises the following steps: Step S1, weighing raw materials by weight, blending nylon slices, thermoplastic polyamide elastomer, modified cellulose and polyvinyl pyrrolidone in a twin-screw extruder for granulation, melt spinning, hot roller drying, oiling and winding, and balance stretching to obtain modified nylon fiber; Further, in step S1, the spinning speed is 1500-1700 m / min, the drafting multiple is 5 times, and the drafting speed is 600 m / min; Step S2, blending the modified nylon fiber and the spandex fiber in a mass ratio of 3-6:4-7 into a modified nylon-spandex yarn, weaving the modified nylon-spandex yarn, and finally washing with alcohol and water in a bath ratio of 1:10 to obtain a highly elastic modified nylon-spandex yarn; Furthermore, in step S2, the alcohol washing is anhydrous ethanol washing for 40-60 minutes, and the water washing is a 70-90° C. water washing for 1-2 hours.

[0007] The invention also proposes the application of the high-elasticity modified nylon-spandex in sportswear.

[0008] Beneficial effects of the present invention: The modified nylon-spandex prepared by the present invention is prepared by blending modified nylon fiber and spandex fiber into yarn and then weaving; the modified nylon-spandex not only has the excellent wear resistance of nylon, but also has the excellent elasticity of spandex, and the nylon fiber is modified to improve the moisture absorption, air permeability and antistatic performance of the modified nylon-spandex. Based on this, the modified nylon-spandex fabric can be widely used in the field of sportswear, yoga wear and other clothing.

[0009] Modified nylon fiber is made of nylon chips as the main raw material, and the addition of thermoplastic polyamide elastomer improves the elasticity of the fiber; the addition of modified cellulose improves the hygroscopicity and antistatic properties of the fiber. This is because the modified cellulose in the nylon fiber can not only use its own hydrophilicity to absorb moisture in the air and form a water film on the surface of the fabric to divert static charge, but also use the ionic liquid grafted on the surface of cellulose to form a conductive network inside the fabric to dissipate the internal static charge. In addition, the large amount of hydrophilic hydroxyl groups contained in the modified cellulose can improve the hygroscopicity of nylon fiber. The increase in hygroscopicity will also cause it to migrate in the fiber, so that the antistatic components can migrate to the surface of the nylon-spandex fabric, compensating for the decrease in antistatic performance caused by the loss of antistatic. In addition, the addition of water-soluble polymer polypyrrolidone can be removed in the later alcohol washing and water washing process, thereby forming gaps inside the fabric and increasing the air permeability and hygroscopicity of the fabric. DETAILED DESCRIPTION

[0010] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0011] Example 1: Modified cellulose is prepared by the following steps: Step A1, dispersing 10 g of cellulose powder in 200 g of 15 wt% sodium hydroxide solution, stirring at 50° C. for 5 h, settling, filtering, washing to neutrality, and drying to obtain alkalized cellulose; Step A2, 0.05 mol of p-toluenesulfonyl chloride was mixed in 20 mL of acetonitrile, recorded as solution 1; 5 g of alkalized cellulose, 1.5 g of sodium hydroxide and 30 mL of water were mixed and stirred evenly, 20 mL of solution 1 was slowly added, and the mixture was reacted in an ice-water bath for 4 h, 50 mL of dichloromethane was added and stirred for 30 min, and the mixture was washed, rotary evaporated and dried to obtain sulfonated cellulose; Step A3, adding 0.5 g of sodium hydroxide and 100 mL of dimethyl sulfoxide to the sulfonylated cellulose obtained in step A2, mixing and stirring evenly, then adding 0.05 mol of 1-vinylimidazole, heating to 75° C. to react for 24 h, distilling under reduced pressure, and drying to obtain quaternary ammonium cellulose; Step A4: Under nitrogen conditions, 8 g of quaternized cellulose, 1 g of methacryloyloxyethyltrimethylammonium chloride and 100 mL of isopropanol were mixed and stirred at 70° C. for 1 h, 0.2 g of azobisisobutyronitrile was added and stirred for 24 h, and the mixture was rotary evaporated, filtered and dried to obtain modified cellulose.

[0012] Example 2: Modified cellulose is prepared by the following steps: Step A1, dispersing 10 g of cellulose powder in 200 g of 15 wt% sodium hydroxide solution, stirring at 50° C. for 6 h, settling, filtering, washing to neutrality, and drying to obtain alkalized cellulose; Step A2, 0.1 mol of p-toluenesulfonyl chloride was mixed in 20 mL of acetonitrile, recorded as solution 1; 7.5 g of alkalized cellulose, 2.3 g of sodium hydroxide and 30 mL of water were mixed and stirred evenly, 20 mL of solution 1 was slowly added, and the mixture was reacted in an ice-water bath for 5 h, 50 mL of dichloromethane was added and stirred for 30 min, and the mixture was washed, rotary evaporated and dried to obtain sulfonated cellulose; Step A3, adding 1 g of sodium hydroxide and 100 mL of dimethyl sulfoxide to the sulfonylated cellulose obtained in step A2, mixing and stirring evenly, then adding 0.1 mol of 1-vinylimidazole, heating to 80° C. and reacting for 30 h, distilling under reduced pressure and drying to obtain quaternary ammonium cellulose; Step A4: Under nitrogen conditions, 10 g of quaternized cellulose, 2 g of methacryloyloxyethyltrimethylammonium chloride and 100 mL of isopropanol were mixed and stirred at 70° C. for 1 h, 0.25 g of azobisisobutyronitrile was added and stirred for 24 h, and the mixture was rotary evaporated, filtered and dried to obtain modified cellulose.

[0013] Example 3: Modified cellulose is prepared by the following steps: Step A1, dispersing 10 g of cellulose powder in 200 g of 15 wt% sodium hydroxide solution, stirring at 50° C. for 7 h, settling, filtering, washing to neutrality, and drying to obtain alkalized cellulose; Step A2, 0.15 mol of p-toluenesulfonyl chloride was mixed in 20 mL of acetonitrile, recorded as solution 1; 10 g of alkalized cellulose, 3 g of sodium hydroxide and 30 mL of water were mixed and stirred evenly, 20 mL of solution 1 was slowly added, and the mixture was reacted in an ice-water bath for 6 h, 50 mL of dichloromethane was added and stirred for 30 min, and the mixture was washed, rotary evaporated and dried to obtain sulfonated cellulose; Step A3, adding 1.5 g of sodium hydroxide and 100 mL of dimethyl sulfoxide to the sulfonylated cellulose obtained in step A2, mixing and stirring evenly, then adding 0.15 mol of 1-vinyl imidazole, heating to 85° C. to react for 36 h, distilling under reduced pressure, and drying to obtain quaternary ammonium cellulose; Step A4: Under nitrogen conditions, 12 g of quaternized cellulose, 3 g of methacryloyloxyethyltrimethylammonium chloride and 100 mL of isopropanol were mixed and stirred at 70° C. for 1 h, 0.3 g of azobisisobutyronitrile was added and stirred for 24 h, and the mixture was rotary evaporated, filtered and dried to obtain modified cellulose.

[0014] Embodiment 4: A method for preparing a highly elastic modified nylon-ammonia comprises the following steps: Step S1, weighing raw materials by weight, blending and granulating 80 parts of nylon slices, 5 parts of thermoplastic polyamide elastomer, 8 parts of modified cellulose prepared in Example 1 and 18 parts of polyvinyl pyrrolidone in a twin-screw extruder, melt spinning, hot roller drying, oiling and winding, and balanced stretching to obtain modified nylon fiber, wherein the spinning speed is 1500m / min, the drafting multiple is 5 times, and the drafting speed is 600m / min; Step S2, blending the modified nylon fiber and the spandex fiber into modified nylon-spandex yarn in a mass ratio of 3:7, then weaving the modified nylon-spandex yarn, and finally washing with alcohol and water in a bath ratio of 1:10 to obtain high-elastic modified nylon-spandex, wherein the alcohol washing is anhydrous ethanol washing for 40 minutes, and the water washing is 70°C water washing for 1 hour.

[0015] Embodiment 5: A method for preparing a highly elastic modified nylon-ammonia comprises the following steps: Step S1, weighing raw materials by weight, blending and granulating 100 parts of nylon slices, 7 parts of thermoplastic polyamide elastomer, 10 parts of modified cellulose prepared in Example 2 and 22 parts of polyvinyl pyrrolidone in a twin-screw extruder, melt spinning, hot roller drying, oiling and winding, and balanced stretching to obtain modified nylon fiber, wherein the spinning speed is 1600m / min, the drafting multiple is 5 times, and the drafting speed is 600m / min; Step S2, blending the modified nylon fiber and the spandex fiber in a mass ratio of 5:5 into a modified nylon-spandex yarn, then weaving the modified nylon-spandex yarn, and finally washing with alcohol and water at a bath ratio of 1:10 to obtain a highly elastic modified nylon-spandex, wherein the alcohol washing is washing with anhydrous ethanol for 50 minutes, and the water washing is washing with water at 80°C for 1.5 hours.

[0016] Embodiment 6: A method for preparing a highly elastic modified nylon-ammonia comprises the following steps: Step S1, weighing raw materials by weight, blending and granulating 120 parts of nylon slices, 9 parts of thermoplastic polyamide elastomer, 12 parts of modified cellulose prepared in Example 3 and 25 parts of polyvinyl pyrrolidone in a twin-screw extruder, melt spinning, hot roller drying, oiling and winding, and balanced stretching to obtain modified nylon fiber, wherein the spinning speed is 1700m / min, the drafting multiple is 5 times, and the drafting speed is 600m / min; Step S2, blending the modified nylon fiber and the spandex fiber in a mass ratio of 6:4 into a modified nylon-spandex yarn, then weaving the modified nylon-spandex yarn, and finally washing with alcohol and water at a bath ratio of 1:10 to obtain a highly elastic modified nylon-spandex, wherein the alcohol washing is washing with anhydrous ethanol for 60 minutes, and the water washing is washing with water at 90°C for 2 hours.

[0017] Comparative Example 1: This comparative example is a nylon-spandex fabric, which differs from Example 6 in that commercially available cellulose is used instead of the modified cellulose prepared in Example 3, and the rest is the same.

[0018] Comparative Example 2: This comparative example is a nylon-spandex fabric, which differs from Example 6 in that the modified cellulose prepared in Example 3 is not added, and the rest are the same.

[0019] Comparative Example 3: This comparative example is a nylon-spandex fabric, which differs from Example 6 in that polyvinyl pyrrolidone is not added, and the rest are the same.

[0020] The high elastic modified nylon-spandex fabrics prepared in Examples 4-6 and the nylon-spandex fabrics prepared in Comparative Examples 1-3 were subjected to performance tests: Elastic elongation test: Tested according to the standard of "FZ / T13019-2007 Yarn-dyed spandex stretch fabric"; Surface resistance test: Tested in accordance with GB / T 22042-2008 "Test method for surface resistivity of antistatic performance of clothing" standard; Hygroscopicity test: Tested in accordance with GB / T 21655.1-2008 "Evaluation of moisture absorption and quick-drying properties of textiles Part 1: Single combination test method"; The test results are shown in Table 1: Table 1: Performance test results

[0021] As can be seen from Table 1, after the elastic elongation, surface resistance and hygroscopicity tests, the elastic elongation of the modified nylon-ammonia prepared by the present invention is (18-20)%, and the surface resistivity is (0.8×10 8 -3.4×10 8 )Ω, and the water absorption rate is (213.4-227.8)%, which shows that the modified nylon-polyamide has the advantages of high elasticity, antistatic and good hygroscopicity, and can be widely used in underwear, sportswear, socks and other fields.

[0022] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A highly elastic modified nylon-ammonia, characterized in that: The modified nylon-spandex is woven from modified nylon-spandex yarn, and the modified nylon-spandex yarn is blended with modified nylon fiber and spandex fiber in a mass ratio of 3-6:4-7; The modified nylon fiber comprises the following raw materials in parts by weight: 80-120 parts of nylon chips, 5-9 parts of thermoplastic polyamide elastomer, 8-12 parts of modified cellulose, and 18-25 parts of polyvinyl pyrrolidone; The modified cellulose is prepared by reacting quaternary ammonium cellulose and methacryloyloxyethyl trimethyl ammonium chloride with azobisisobutyronitrile as the initiator; the quaternary ammonium cellulose is prepared by reacting sulfonated cellulose with 1-vinyl imidazole; the sulfonated cellulose is prepared by reacting alkalized cellulose with p-toluenesulfonyl chloride; and the alkalized cellulose is prepared by alkalizing cellulose powder in a sodium hydroxide solution.

2. A highly elastic modified nylon-ammonia according to claim 1, characterized in that: The modified cellulose is prepared by the following steps: Step A1, dispersing cellulose powder in 15wt% sodium hydroxide solution, stirring at 50°C for 5-7h, settling, filtering, washing to neutrality, and drying to obtain alkalized cellulose; Step A2, mixing p-toluenesulfonyl chloride in acetonitrile, recorded as solution 1; mixing alkalized cellulose, sodium hydroxide and water, stirring evenly, slowly adding solution 1, reacting in an ice-water bath for 4-6 hours, adding dichloromethane and stirring for 30 minutes, washing, rotary evaporation, and drying to obtain sulfonated cellulose; Step A3, adding sodium hydroxide and dimethyl sulfoxide to the sulfonylated cellulose obtained in step A2, mixing and stirring evenly, then adding 1-vinylimidazole, heating to 75-85° C. and reacting for 24-36 hours, distilling under reduced pressure and drying to obtain quaternary ammonium cellulose; Step A4: Under nitrogen conditions, quaternized cellulose, methacryloyloxyethyltrimethylammonium chloride and isopropanol are mixed and stirred at 70° C. for 1 h, azobisisobutyronitrile is added and stirred for 24 h, and the mixture is rotary evaporated, filtered and dried to obtain modified cellulose.

3. A highly elastic modified nylon-ammonia according to claim 2, characterized in that: In step A1, the mass ratio of cellulose powder to sodium hydroxide solution is 1:

20.

4. A highly elastic modified nylon-ammonia according to claim 2, characterized in that: In step A2, the amount ratio of alkalized cellulose, sodium hydroxide, water, solution 1 and dichloromethane is 5-10 g:1.5-3 g:30 mL:20 mL:50 mL, and the amount ratio of p-toluenesulfonyl chloride and acetonitrile in solution 1 is 0.05-0.15 mol:20 mL.

5. A highly elastic modified nylon-ammonia according to claim 2, characterized in that: In step A3, the molar ratio of 1-vinylimidazole to p-toluenesulfonyl chloride in step A2 is 1:1, and the amount of sodium hydroxide is 0.5-1.5 g.

6. The high elastic modified nylon-ammonia according to claim 2, characterized in that: In step A4, the usage ratio of quaternized cellulose, methacryloyloxyethyltrimethylammonium chloride, isopropyl alcohol and azobisisobutyronitrile is 8-12 g:1-3 g:100 mL:0.2-0.3 g.

7. A method for preparing the highly elastic modified nylon-ammonia according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, blending nylon slices, thermoplastic polyamide elastomer, modified cellulose and polyvinyl pyrrolidone in a twin-screw extruder for granulation, melt spinning, hot roller drying, oiling and winding, and balance stretching to obtain modified nylon fiber; Step S2, blending the modified nylon fiber and the spandex fiber in a mass ratio of 3-6:4-7 into a modified nylon-spandex yarn, weaving the modified nylon-spandex yarn, and finally washing with alcohol and water in a bath ratio of 1:10 to obtain a highly elastic modified nylon-spandex yarn.

8. The method for preparing highly elastic modified nylon-ammonia according to claim 7, characterized in that: Step S1, the spinning speed is 1500-1700 m / min, the drafting multiple is 5 times, and the drafting speed is 600 m / min.

9. The method for preparing highly elastic modified nylon-ammonia according to claim 7, characterized in that: In step S2, the alcohol washing is anhydrous ethanol washing for 40-60 minutes, and the water washing is a 70-90° C. water washing for 1-2 hours.

10. Use of the highly elastic modified nylon-spandex according to claim 1 in sportswear.

Citation Information

Patent Citations

  • Preparation method of amphoteric grafting-type modified cellulose flocculant

    CN104017136A

  • Anti-static moisture absorption polyacrylonitrile fiber, anti-static moisture absorption fabric, preparation method and application

    CN107503136A

  • Cellulose quaternary ammonium salt adsorbing agent, and preparation method and application thereof

    CN108404885A

  • High-elasticity chinlon-spandex wrap yarn, preparation method thereof and application of high-elasticity chinlon-spandex wrap yarn in fabric

    CN117587561A

  • High-elasticity cool-feeling bio-based fabric, preparation method thereof and application of high-elasticity cool-feeling bio-based fabric in underwear

    CN118257019A

Cited By

  • High-elastic anti-static modified chinlon fabric and preparation method thereof

    CN120443461A